2019
DOI: 10.1111/hsc.12714
|View full text |Cite
|
Sign up to set email alerts
|

Actions to influence the care network of home‐dwelling elderly people: A qualitative study

Abstract: Positive impact of care networks of home‐dwelling elderly people may be based on several network mechanisms: navigation to resources, negotiation between participants and contagion of behaviours. Little is known about actions of participants—elderly people, informal caregivers or formal care providers—to activate such mechanisms and generate support. Aim of this study was to identify actions in relation to these network mechanisms. A cross‐sectional qualitative study of 48 interviews with home‐dwelling elderly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…We are uncertain to what extent healthcare professionals and patients recognize and report network-related processes. Previous studies suggested that the range of factors, mechanisms and processes is substantially broader than perceived and reported by patients or providers in interviews [28].…”
Section: Discussionmentioning
confidence: 95%
“…We are uncertain to what extent healthcare professionals and patients recognize and report network-related processes. Previous studies suggested that the range of factors, mechanisms and processes is substantially broader than perceived and reported by patients or providers in interviews [28].…”
Section: Discussionmentioning
confidence: 95%
“…A proxy can ll holes in the network left by age-related changes and life events (3,21). Creating a proxy in informal or formal care is an intervention applied by informal and formal care to organise contact and distance themselves from interaction in the network of informal caregivers (2). However, the proxy network is vulnerable because changes in the network are dependent on this often informal proxy.…”
Section: Discussionmentioning
confidence: 99%
“…With ageing populations and spending cuts in public healthcare, western countries are increasingly focusing on ageing at home with support from a network that is comprised of the older person's social network with or without formal care providers (1). Networks exhibit diversity in their constellations and the support they generate (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…With ageing populations and spending cuts in public healthcare, western countries are increasingly focusing on ageing at home with support from a network that is comprised of the older adult’s social network with or without formal care providers [ 1 ]. Networks exhibit diversity in their constellations and the support they generate [ 2 4 ]. In order to improve the generated support from networks, it is important for formal care providers to know network composition and understand interaction processes in the network (network mechanisms).…”
Section: Introductionmentioning
confidence: 99%